![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1. -x+20 = -(-15)-8+13
=> -x=15-8+13-20
=> -x=0
=> x=0
2. -(-10)+x=-13+(-9)+(-6)
=> 10+x=-13-9-6
=> x = -13-9-6-10
=> x = -38
3. 8-(-12)+10=-(-14)-x
=> 8+12+10=14-x
=> x = 14-8-12-10
=> x = -16
4. -(+12)+(-x)-(-3)=5-(-7)
=> -12-x+3=5+7
=> -x=5+7+12-3
=> -x=21
=> x=-21
5. 14-x+(-10)=-(-9)+(+15)
=> 14-x-10=9+15
=> -x=9+15-14+10
=> -x=20
=> x=-20
6. 12-(-17)+(-3)=-5+x
=> 12+17-3+5=x
=> x=31
7. x-(-19)-(+32)=14-(+16)
=> x+19-32=14-16
=> x=14-16+32-19
=> x=11
8. x-|-15|-|7|=-(-9)+|-5|
=> x-15-7=9+5
=> x=9+5+7+15
=> x=36
9. 15-x+17=13-(-21)
=> 15-x+17=13+21
=> -x=13+21-15-17
=> -x=2
=> x=-2
10. -|-5|-(-x)+4=3-(-25)
=> -5+x+4=3+25
=> x=3+25-4+5
=> x=29
![](https://rs.olm.vn/images/avt/0.png?1311)
a . 13-|x+5|=14
\(\Rightarrow Ix+5I=-1\)
\(\Rightarrow x\in\varnothing\)
b.27-3 | x-2|=15
\(3Ix-2I=12\)
\(|x-2|=4\)
\(\Rightarrow\orbr{\begin{cases}x-2=4\\x-2=-4\end{cases}\Leftrightarrow\orbr{\begin{cases}x=6\\x=-2\end{cases}}}\)
c 10+|x-15|=3
\(Ix-15I=-7\)
\(\Rightarrow x\in\varnothing\)
2 Tìm số nguyên a sao cho
a -32 (a+21)=0
\(a+21=0\)
\(a=-21\)
b (a+1) (a-2)=0
\(\Rightarrow\orbr{\begin{cases}a+1=0\\a+2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-1\\a=-2\end{cases}}}\)
c 15+a^2=24
\(a^2=9\)
\(a=\pm3\)
học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
1, -15 + \(x\) = -14 - (-57)
-15 + \(x\) = -14 + 57
\(x\) = -14 + 57 + 15
\(x\) = 43 + 15
\(x\) = 58
2, (-14) + \(x\) - 7 = -10
-14 + \(x\) - 7 = -10
- 21 + \(x\) = - 10
\(x\) = -10 + 21
\(x\) = 11
![](https://rs.olm.vn/images/avt/0.png?1311)
a , 32 - 2 ( x + 1 ) = 42
2 ( x + 1 ) = 32 - 42
2 ( x + 1 ) = -10
x + 1 = -10 : 2 = -5
x = -5 - 1 = -6
b, 12 - 5 (x + 2 ) = 32
5 ( x + 2 ) = 12 - 32 = -20
x + 2 = -20 : 5 = -4
x = -4 - 2 = -6
c , 14 - 5 ( x + 4 ) = 9
5 ( x + 4 ) = 14 - 9
5 ( x + 4 ) = 5
x + 4 = 5 : 5 = 1
x = 1 - 4 = -3
d , 24 - 6 ( 2x + 1 ) = 6
6 ( 2x + 1 ) = 24 - 6
6 ( 2x + 1 ) = 18
2x + 1 = 18 : 6
2x + 1 = 3
2x = 3 - 1 = 2
x = 2 : 2 = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
17x + 3. ( -16x – 37) = 2x + 43 - 4x
<=>17x-48x-111=-2x+43
<=>-29x=154
<=> \(x=-\frac{154}{29}\)
-3. (2x + 5) -16 < -4. (3 – 2x)
\(\Leftrightarrow-6x-31< -12+8x.\)
\(\Leftrightarrow-14x< 19\Rightarrow x< -\frac{19}{14}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(-3+x=5-\left(-7\right)\)
\(\Leftrightarrow-3+x=5+7\)
\(\Leftrightarrow-3+x=12\)
\(\Leftrightarrow x=12+3\)
\(\Leftrightarrow x=15\)
Vậy x= 15
\(x-2=2x-7\)
\(\Leftrightarrow x-2+7=2x\)
\(\Leftrightarrow x-\left(2-7\right)=2x\)
\(\Leftrightarrow2-7=x-2x\)
\(\Leftrightarrow-5=-x\)
\(\Leftrightarrow x=5\)
Vậy x= 5
32-3x=3+14
32-3x=17
3x=32-17
3x=15
X=15:3
X=5
x:29-3x= 19
2x-29=19
2x= 48
x= 48:2
x= 24